RECOMMENDATIONS FOR INCLUDING DIALECTAL WORDS IN AN EXPLANATORY DICTIONARY - Khasanov Abdumannon Majidovich (Journals Park Publishing, 2024)
This article deals with the inclusion of dialect words in explanatory dictionaries that describe the lexical norms of the Uzbek literary language. Lexicographic experiments on the inclusion of dialect words in the standard dictionary are studied and their general criteria are described. The experience gained on this issue was analyzed and proposals were made on some of its aspects.
Keywords: Vocabulary, lexical standard, dialect, explanatory dictionary, dialect word, literariness, lexical development.